Evaluation of Combined Spectral Enhancement and Phase Adjustment in Hearing-Aids - Zeyl, Timothy J. (My University, 2010)
p.p1 {margin: 0.0px 0.0px 0.0px 0.0px; font: 11.5px Times; color: #585858} p.p2 {margin: 0.0px 0.0px 0.0px 0.0px; font: 11.5px Times; color: #6f6f6f} p.p3 {margin: 0.0px 0.0px 0.0px 0.0px; font: 11.5px Times; color: #424242} span.s1 {color: #424242} span.s2 {color: #6f6f6f} span.s3 {color: #585858} span.s4 {color: #8d8d8d}
Auditory nerve fibers in an ear with outer hair cell damage can be conceptualized as filters having a broadened frequency response area, a shallower phase response and a shorter group delay with respect to a healthy fiber, particularly at low stimulus presentation levels. As well, the presence of inner hair cell damage requires increased stimulus presentation levels for restoration of fiber discharge rates, which results in broad auditory filters with shallow phase response and short group delay. As a consequence, the discharge times in the impaired ear in response to a tone stimulus are more coincident across a population of fibers with a range of characteristic frequencies. This behaviour resembles the spatiotemporal response pattern in a healthy auditory periphery in response to loud stimuli and has been postulated as a potential correlate to loudness recruitment. Commercial hearing aids do not address any changes in the phase characteristics of impaired auditory nerve fibers.
The present study evaluates the potential for correction of the altered temporal p.p1 {margin: 0.0px 0.0px 0.0px 0.0px; font: 11.5px Times; color: #585858} p.p2 {margin: 0.0px 0.0px 0.0px 0.0px; font: 11.5px Times; color: #6f6f6f} span.s1 {color: #6f6f6f} span.s2 {color: #424242} span.s3 {color: #585858} span.s4 {font: 11.0px Times} span.s5 {font: 11.0px Times; color: #585858} span.s6 {font: 11.0px Times; color: #8d8d8d} span.s7 {color: #8d8d8d} span.s8 {font: 11.0px Times; color: #6f6f6f} span.s9 {font: 11.0px Times; color: #a1a1a1}
relationships in the neural firing pattern of the impaired ear by a hearing aid. An improved version of the spatiotemporal pattern correction (SPC) scheme (Shi et al., 2006) is presented, which measures the instantaneous difference in group delay between a bank of model healthy and impaired auditory nerve fibers and inserts the corresponding delays into an analysis-synthesis gammatone filterbank in t he hearing aid. Human testing of the original processing scheme showed that listeners preferred unprocessed sounds over processed sounds and that no systematic improvement in speech intelligibility was provided by the processed speech (Shi et al. , 2006; Calandruccio et al. , 2007). However, no computational analysis of t his scheme was reported and no attempts were made to restore synchrony to the formants of voiced speech in the neural response. To address this issue, the current work pre-processes SPC with an updated version of the multiband and improved, contrast-enhanced frequency shaping (MICEFS) algorithm (Harte et al. , 2006) to restore formant synchrony.
These processing schemes are evaluated with a computational model of the auditory p.p1 {margin: 0.0px 0.0px 0.0px 0.0px; font: 11.5px Times; color: #6f6f6f} p.p2 {margin: 0.0px 0.0px 0.0px 0.0px; font: 11.5px Times; color: #585858} span.s1 {color: #585858} span.s2 {color: #424242} span.s3 {color: #8d8d8d} span.s4 {color: #6f6f6f}
periphery (Zilany and Bruce, 2006, 2007) in response to a synthesized vowel for a
number of hearing loss types. Analysis indicates that SPC disrupts the spatiotemporal
response, but some synchrony can be preserved if the signal is pre-processed with
MICEFS and if the SPC delays are applied at the appropriate time. There are some technical problems associated with the processing scheme discovered in this study that remain unresolved. These include: i) a non-fiat frequency response through the analysis-synthesis filterbank due to changes in the relative temporal alignment of filterbank channels, ii) group delay corrections that are based on potentially incorrect frequencies due to the spread of synchrony in audit ory nerve responses, and iii) frequency modulations in the processed signal creat ed by the insertion of time-varying delays, which results in noise that is audible to normal listeners. Despite these issues, evaluation with an error metric derived from auditory nerve response cross-correlations shows that this processing scheme improves some features of the spatiotemporal response, even though it degrades others.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering